2011
DOI: 10.1007/s11606-011-1885-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Appreciative Inquiry Approach to Improve Resident Sign-Out in an Era of Multiple Shift Changes

Abstract: Resident views toward sign-out are diverse, and accuracy of written records may be limited. Consecutive sign-outs are associated with degradation of information. An appreciative-inquiry approach capitalizing on exemplar residents was effective at creating standards for sign-out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…Students confi rmed that they were optimistic about the future and, faced with the possibility of working in teams with collaborative practices between workers with diff erent backgrounds (20) , which is in line with the results of this study, where it was identifi ed that residents value and realize the importance of teamwork, combined with the pleasure provided by integration in multidisciplinary work.…”
Section: Today We Do Not Work Much In the Professional Core It' S Mosupporting
confidence: 85%
“…Students confi rmed that they were optimistic about the future and, faced with the possibility of working in teams with collaborative practices between workers with diff erent backgrounds (20) , which is in line with the results of this study, where it was identifi ed that residents value and realize the importance of teamwork, combined with the pleasure provided by integration in multidisciplinary work.…”
Section: Today We Do Not Work Much In the Professional Core It' S Mosupporting
confidence: 85%
“…16,17 Moreover, methods such as appreciative inquiry can help identify the peers with the best practices to emulate. 18 Future efforts to validate peer assessment of handoffs against these other assessment methods, such as direct observation by service attendings, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent, appreciative-inquiry study 7 in a large internal medicine training program found that handoffs varied widely in the absence of an educational curriculum and that a consistent methodology for sign-out organization is key.…”
Section: What Is Knownmentioning
confidence: 99%